Strategies in the development of pro-oxidant therapy for oral squamous cell carcinoma: a scoping review - Niazi, Zainab; Mujtaba, Hassan; Ibrahim, Nurul Ruziantee; Murtey, Mogana D.; Yusop, Norhayati (Elsevier B.V., 2025)
Background: Pro-oxidant therapy has gained attention as newly potential approach in combating oral cancer. However, there are lack of classification and comparative analysis on extensive literatures which focuses on the different strategies and efficacy of pro-oxidant based therapies. This review aims to investigate the develop- ment of pro-oxidant therapy in treatment of oral cancer, emphasising on the fundamental knowledge behind each method, the impacts of each pro-oxidant-based method on cancer cell lines, and the future application in clinical practices. Method: The present scoping review is carried out according to the Arksey and O’Malley framework’s four-stage scoping review technique. The search was conducted from different electronic research databases such as Google Scholar, Web of Science, PubMed, and Scopus to select relevant peer-reviewed studies. The search strategy includes keywords such as “strategies” “development”, “pro-oxidant”, therapy”, “oral”and “squamous cell carcinoma”. The articles were screened, by keeping in mind the inclusion and exclusion criteria, along with assessment for eligibility. The present study is registered with Open Science Framework (OSF), followed by PRISMA-ScR guidelines to increase the relevance for decision-making. Results: 313 articles were selected by searching the literature databases, 250 were identified relevant to the present scoping review topic. Following the screening criteria, only 15 articles were included in the final review for detail analysis. Conclusions: The gathered data positively contribute to more discoveries of advanced techniques for the management of cancer with minimal toxicities to improve on treatment outcomes.